Fractured feminisms : rhetoric, context, and contestation - Gray-Rosendale, Laura; Harootunian, Gil, 1957- (State University of New York Press, 2003)
"Fractured Feminisms resists and reshapes boundaries by investigating how gender studies' intersection with race and ethnicity, class, postcoloniality, sexuality, globalization, interdisciplinarity, technology studies, and administration exposes the "silenced other" of feminisms themselves. These crucial conversations about feminisms depend upon facing the perplexing rhetorical problems within feminist debates, yet work within these fractures to discover newly emerging, productive feminist practices. This book contends that it's important to better understand the ways in which feminist rhetorics both empower and constrain and the kinds of identities feminisms afford as well as deny."--Jacket